LEARNING-RELATED SOCIAL SKILLS AS A MEDIATOR BETWEEN TEACHER INSTRUCTION AND CHILD ACHIEVEMENT IN HEAD START - Ansari, Arya (Soc Dev, 2015)
Using a subsample of the Family and Child Experiences Survey (FACES) 2006, this study examined the associations between the amount of teacher instruction in 292 Head Start classrooms with changes in young children’s (n = 936) early academic achievement and learning-related social skills from ages 3 to 5. In general, during the early years, children exhibited relatively stable academic and learning-related social skills. Although the amount of teacher instruction did not predict children’s short-term academic growth directly, it did predict it indirectly through improvements in learning-related social skills, with benefits lasting through the end of kindergarten. These findings demonstrate that gains in children’s learning-related social skills may be necessary before academic gains can be realized.